The value-added genome: building and maintaining genomic cytosine methylation landscapes - Rangwala, Sanjida H; Richards, Eric J (Current opinion in genetics & development, 2004)
Epigenetic marks, such as cytosine methylation and post-translational histone modifications, are important for interpreting and managing eukaryotic genomes. Recent genetic studies in plants have uncovered details on the different interwoven mechanisms that are responsible for specification of genomic cytosine methylation patterns. These mechanisms include targeting cytosine methylation using heterochromatic histone modifications and RNA guides. Genomic cytosine methylation patterns also reflect locus-specific demethylation initiated by specialized DNA glycosylases. While genetics continues to more fully define these mechanisms, genomic studies in Arabidopsis have yielded an unprecedented high-resolution view of how epigenetic marks are layered over a genome.